Daytime, low latitude, vertical ExB drift velocities, inferred from ground-based magnetometer observations in the Peruvian, Philippine and Indian longitude sectors under quiet and disturbed conditions - Anderson, D.; Anghel, A.; Chau, J.; Yumoto, K.; Bhattacharyya, A.; Alex, S. (My University, 2006)
Recent studies have demonstrated that ground-based magnetometer observations can be used to infer realistic, daytime vertical ExB drift velocities in the Peruvian longitude sector. It has also been demonstrated that under certain conditions the time variability of the Interplanetary Electric Field (IEF) – minutes to hours – is reflected in the daytime, prompt penetration of high latitude electric fields to low latitudes. In this paper, we incorporate magnetometer-inferred ExB drift techniques to extend this study to include the Philippine and Indian sector ExB drift velocities and to investigate the relationships between IEF conditions and daytime, low latitude electric field observations under both geomagnetically quiet and disturbed conditions. This paper addresses two basic questions: 1.) How well do the quiet-time, ΔH-inferred ExB drift velocities compare with the Fejer-Scherliess, quiet-time, climatological model (Scherliess and Fejer, 1999) in the Peruvian, Philippine and Indian sectors and 2.) What are the relationships between the Interplanetary Electric Fields (IEF) and low latitude electric fields during disturbed periods? We address the above questions by analyzing magnetometer-inferred ExB drift velocities between January 2001 and December 2004 when there exists more than 450 quiet days and more than 235 geomagnetically disturbed days, defined by daily Ap values greater than 20. It is demonstrated that the neural network approach that provides realistic ExB drift velocities based on magnetometer observations in the Peruvian sector can be applied at all longitudes where appropriately placed magnetometers exist. It is found that 1.) The average quiet, daytime upward ExB drift velocity vs Local Time is comparable to the Fejer-Scherliess climatological model and 2.) During disturbed conditions, it is observed that promptly penetrating electric fields occur, simultaneously, in the Philippine, Indian and Peruvian sectors.
Keywords: Equatorial electrojet; Low latitude ExB drifts; Interplanetary electric fields; Magnetometer observations